The Role of Notaries in Making Marriage Agreement Deeds After the Constitutional Court Decision Number 69/PUU-Xlll/2015 in 2015 - Izza, Karelina Fatimatun (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
Problems in marriage certainly result in very systematic legal consequences, especially regarding the rights and obligations of husband and wife, the legal status of husband and wife, family assets and children born in marriage, and assets of husband and wife that are not clearly regulated are feared to cause a mixture of the assets brought by each party and cause problems between the two parties. The purpose of this study is to analyze the implementation of the Marriage Agreement before and after the Constitutional Court Decision Number 69/PUU-Xlll/2015 and to determine the role of the Notary in relation to the preparation of the Marriage Agreement deed after the Constitutional Court Decision Number 69/PUU-Xlll/2015. The research method used is the Sociological legal approach method, namely research that focuses on the legal science aspect and connects the legal rules that apply in society. This approach method is used because it focuses on existing legislation and is related to practice in the field. From the results of the analysis and discussion regarding the role of Notaries in making Marriage Agreement Deeds after the Constitutional Court Decision Number 69/PUU-Xlll/2015, it can be concluded that before the Constitutional Court decision, marriage agreements can only be made before the marriage takes place, while after the Constitutional Court decision, marriage agreements can be made before and during the marriage takes place and Notaries still have the authority to make marriage agreement deeds. The mechanism used is to write down the wishes of the husband and wife by applying Article 1338 of the Civil Code concerning the freedom to make contracts and Article 1320 of the Civil Code concerning the valid requirements for agreements.